Luís Bernardino. Angola in the African Peace and Security Architecture: The Strategic Role of the Angolan Armed Forces. Lisboa: Mercado das Letras. 2017. 543 pp. - Almeida, E. C. (Cadernos de Estudos Africanos, 2018)
Análise ao livro de Luís Manuel Brás Bernardino sobre as Forças Armadas de Angola, «Angola in the African Peace and Security Architecture: The Strategic Role of the Angolan Armed Forces» _____ Analysis to the book of Luis Manuel Bernardino Brás on the Angola Armed Forces, "Angola in the African Peace and Security Architecture: The Strategic Role of the Angolan Armed Forces»